Perception regarding the management of defective composite restorations in dental colleges of Pakistan: Repair versus Replacement; a Cross-sectional study - Asma Munir khan (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Minimal intervention dentistry (MID) has shifted the trend towards repairing rather than replacing direct composite restorations in case already existing restoration becomes defective. Repairing these restorations has many benefits, such as preservation of tooth structure, improved prognosis, cost-effectiveness, and reduced need for local anesthesia. However, the decision-making process for managing local defects in composite restorations can be challenging for dentists. This study aimed to investigate the knowledge and practices for managing defective direct composite restorations in dental colleges in Pakistan.A cross-sectional survey was conducted on 297 participants, which included 3rd and 4th-year dental students, house officers, and operative dentistry residents. A previously validated survey instrument was used for data collection via Google Forms.SPSS was used for the data analysis.The results showed that most participants were taught about composite repair during their undergraduate studies. However, most participants had not repaired and replaced a defective composite restoration. The study also found a significant association between the participants' level and their preference for restoration repair vs replacement. Additionally, the study revealed that the majority of participants preferred flowable composites as their repair material, and there was a significant association between the participants' academic year and their preferred repair material for defective restoration. The most commonly used technique for finishing was with diamond finishing instruments.The study suggests that there is a need for scientific societies and workgroups in restorative and operative dentistry to produce guidelines on key treatment steps for repairing defective composite restorations.